Learning Potential in Narrative Writing: Measuring the Psychometric Properties of an Assessment Tool - Gurgel, Léia G.; de Oliveira, Mônica M. C.; Joly, Maria C. R. A.; Reppold, Caroline T. (Frontiers in Psychology, 2017)
Objective: The Computerized and Dynamic Writing Test (TIDE) is designed to examine the learning potential of adolescents in narrative writing. This was a validation study of the TIDE based on its internal structure. Learning potential is responsible for cognitive modifiabilty according to the Theory of Cognitive Structural Modifiability developed by Feüerstein. Method: Included 304 participants between 10 and 17 years of age from schools in the South of Brazil. The data collection involved student groups that were divided according to age and school grade. Each participant reponded to the TIDE for an average of 50 minutes in the school's computer lab. The participants’ selection criteria were: being regularly enrolled in the fifth to eighth grade and providing an informed consent form signed by a responsible caregiver. The exclusion criteria included: neurological problems, having been held back in school for two or more years, not cooperating, not completing the test for any reason and physical conditions impeding the assessment. Results: The Kendall test indicated agreement between two evaluators, who corrected the participants’ first and second texts that resulted from applying the TIDE. The TIDE is divided into three modules. Factor analysis was applied to the first module (pre-test), which revealed a division in two factors, and to the second module (instructional module), which was divided in three factors. The reliability of the TIDE items was verified using Cronbach’s Alpha with coefficients greater than 0.7. The analysis of the third module (post-test) was based on McNemar’s Test and showed statistically significant results that demonstrated an evolution in the participants’ learning potential. Conclusion: The TIDE proved to be valid and is considered a relevant tool for speech, language, hearing, psychological and educational assessment. The original nature of the tool presented here is highlighted, based on the dynamic assessment method, offering data on a narrative writing learning method as well as its possible adaptation to other contexts and languages. In addition, the computer-based nature of the tool is emphasized, enabling its more precise application and analysis of participant performance, in addition to its lower cost, reduced application bias.